PENGARUH ATTACHMENT TERHADAP ORIENTASI PERILAKU PROSOSIAL PADA REMAJA DI SEKOLAH MENENGAH ATAS NEGERI (SMAN) 2 BEKASI - Eva Wulandari (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
Abstract This research is aimed to analyze the effect of attachment on orientation prosocial behavior of Adolescents. The research was conducted at 2 State High School of Bekasi. The method used in this study is quantitative research methods using the Ex Post Facto design. The sampling technique in this study is proportionate stratified probability sampling with random sampling. The number of samples used in this study as many as 100 people. Data analysis techniques are used to test the hypothesis is to test the regression by using SPSS 20. Based on the results of a calculation, a large effect (Adjusted R Square) variable attachment to orientation of prosocial behavior were 0.123 (12.3%), which means that attachment affects orientation of prosocial behavior as much as 12.3% and the remaining 87.7% is influenced by factors other than attachment. The results showed Ha received so it can be concluded that there is influence of attachment on orientation of prosocial behavior in adolescents in State High School (SMAN) 2 Bekasi. Keywords: Attachment, Orientation, Prosocial Behavior, Adolescents